Polymer-based composite solid electrolyte, preparation method and sodium solid-state battery
By using nitrided nanoTiO2 filler in polymer-based composite solid electrolytes, the problems of low ionic conductivity and poor mechanical properties of polymer-based composite solid electrolytes are solved, and high ionic conductivity, wide electrochemical stability window and good Comprehensive improvement of mechanical performance.
Patent Information
- Application Number
- CN202510031360.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing polymer-based composite solid electrolytes have low ionic conductivity and poor mechanical properties at room temperature, making it difficult to achieve practicality.
Using nitrided nano-TiO2 as functional filler, TiO2 powder was nitrided in a mixture of argon and nitrogen by plasma treatment to prepare a high-performance polymer-based composite solid electrolyte.
The ionic conductivity and electrochemical stability window of solid electrolytes are significantly improved, mechanical properties are enhanced, and the formation of good SEI is promoted, and the cycle stability of the battery is improved.
Smart Images

Figure CN119419355A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polymer-based composite solid electrolyte, a preparation method and a sodium solid-state battery, and in particular to a nitrided nano-TiO 2 The invention relates to a reinforced polymer-based composite solid electrolyte, a preparation method and a sodium solid-state battery, belonging to the technical field of solid-state batteries. Background Art
[0002] Due to the abundance of sodium resources and low cost, rechargeable sodium-ion batteries have received increasing attention in large-scale fixed energy storage. However, when using liquid electrolytes, the inherent volatility and flammability of organic electrolytes can pose serious safety hazards. Solid electrolytes have high safety and high electrochemical stability, which can better solve the above problems. Among various solid electrolytes, polymer solid electrolytes are considered to be the most likely solid electrolytes to be applied to commercial solid-state batteries due to their good interface compatibility, flexibility and large-scale preparation. However, polymer solid electrolytes have been seriously hindered in their practical application due to their low room temperature ionic conductivity and poor mechanical properties. Compared with polymer solid electrolytes, composite solid electrolytes combine polymers and inorganic ceramics to achieve high ionic conductivity and high mechanical strength, and are considered to be the most promising candidates for the practical application of solid-state batteries. At present, although many kinds of fillers are used to improve the performance of composite solid electrolytes, they can improve the ionic conductivity and battery stability of composite solid electrolytes to a certain extent, as well as special requirements such as mechanical properties and flame retardancy. However, it is difficult to improve the comprehensive performance of ionic conductivity, electrochemical stability window and battery cycle performance by adding ordinary inorganic fillers. This is because ordinary inorganic fillers can only reduce the glass transition temperature of the polymer and improve the activity of the co-chain segment, but have little effect on the electrochemical stability window. At the same time, ordinary inorganic fillers have no effect on the composition and structure of the interface layer (SEI), making it difficult to improve the cycle stability of the battery, and may even bring other adverse effects. Summary of the invention
[0003] In view of the shortcomings of the prior art, one of the objects of the present invention is to provide a polymer-based composite solid electrolyte with high ionic conductivity and a wide electrochemical stability window; a second object of the present invention is to provide a method for preparing a polymer-based composite solid electrolyte; a third object of the present invention is to provide a sodium solid-state battery.
[0004] In order to solve the above technical problems, the technical solution of the present invention is as follows: A polymer-based composite solid electrolyte, comprising 8-12 parts of an olefin polymer, 4-8 parts of a sodium salt and 0.2-2.4 parts of a filler, wherein the filler is nitrided nano-TiO 2 ; Wherein, the nitrided nano-TiO 2The preparation method is as follows: in a mixed gas of argon and nitrogen, TiO is treated with plasma at 200-400°C 2 Powder 0.1-2h, obtain nitrided nano-TiO 2 ; Among them, the concentration of nitrogen in the mixed gas is 5-30 vol%; the flow rate of the mixed gas is 40-60 ml / min, the pressure is 0.18-0.45 Pa, and the power of plasma treatment is 200-450 W.
[0005] Optionally, the polymer-based composite solid electrolyte comprises 9-11 parts of olefin polymer, 5-7 parts of sodium salt and 0.4-2.2 parts of filler.
[0006] Optionally, the polymer-based composite solid electrolyte comprises 9.5-10.5 parts of olefin polymer, 5.5-6.5 parts of sodium salt and 0.6-2 parts of filler.
[0007] Further, the vinyl polymer is one or more of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene) copolymer, poly(vinylidene fluoride-trifluoroethylene) copolymer, poly(vinylidene fluoride-tetrafluoroethylene) copolymer and poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) copolymer. Optionally, the weight average molecular weight of the vinyl polymer is 30-50W, and further 35-45W.
[0008] Furthermore, the sodium salt is one or more of sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, sodium hexafluorophosphate, sodium difluorophosphate, sodium tetrafluoroborate, sodium difluorooxalatoborate, sodium bisoxalatoborate and sodium perchlorate.
[0009] Furthermore, in the mixed gas, the concentration of nitrogen is 10-25 vol%, preferably 15-20 vol%; the flow rate of the mixed gas is 45-55 ml / min, preferably 48-52 ml / min, the pressure is 0.2-0.42 Pa, preferably 0.25-0.38 Pa, and the power of plasma treatment is 240-420 W, preferably 280-380 W.
[0010] Optionally, TiO 2 The particle size of the powder is less than 500 nm. 2 The particle size of the powder is <300nm.
[0011] Furthermore, the thickness of the polymer-based composite solid electrolyte is 20-200 μm, preferably 40-180 μm, and more preferably 60-160 μm.
[0012] Optionally, the polymer-based composite solid electrolyte further includes a polar solvent.
[0013] Based on the same inventive concept, the present invention also provides a method for preparing the polymer-based composite solid electrolyte as described above, comprising the following steps: S1. Evenly mix the vinyl polymer, sodium salt, filler and polar solvent in a ratio of 8-12 g: 4-8 g: 0.2-2.4 g: 20-60 ml to obtain a polymer solution; S2. Casting the polymer solution on a mold, removing the solvent, and obtaining a polymer-based composite solid electrolyte.
[0014] Further, in S1, the olefinic polymer, sodium salt, filler and polar solvent are uniformly mixed in a ratio of 8-12g:4-8g:0.2-2.4g:25-55ml. Preferably, the olefinic polymer, sodium salt, filler and polar solvent are uniformly mixed in a ratio of 9-11g:5-7g:0.3-2g:35-45ml.
[0015] Furthermore, in S1, the polar solvent is one or more of tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, acetone and 2,2,2-trifluoro-N,N-dimethylacetamide.
[0016] Further, in S1, the vinyl polymer, sodium salt, filler and polar solvent are mixed and stirred at 45-80° C. for 6-14 hours. Optionally, the vinyl polymer, sodium salt and polar solvent are first mixed uniformly, and then the filler is added and mixed uniformly.
[0017] Furthermore, in S2, when removing the solvent, first dry at 25-45°C for 0.2-2h, then dry at 40-60°C for 0.5-3h, and then dry at 55-80°C for 1-5h; preferably, the dew point of the drying environment is less than -40°C, or the drying environment is a vacuum environment (such as a vacuum drying device) or a protective atmosphere environment (such as a glove box); preferably, the temperature of each drying stage increases in sequence. This helps to obtain a polymer-based solid electrolyte membrane with better quality.
[0018] Preferably, the mold is a glass plate or a polytetrafluoroethylene mold.
[0019] Based on the same inventive concept, the present invention also provides a sodium solid-state battery, comprising a positive electrode plate stacked in sequence, a polymer-based composite solid electrolyte as described above or a polymer-based composite solid electrolyte prepared by the preparation method as described above, and a negative electrode.
[0020] Optionally, the active material in the positive electrode plate is a conventional commercial sodium battery positive electrode material, and other components of the positive electrode plate are a conductive agent (such as SP), a binder (such as PVDF), an ion conductor or other functional additives that are beneficial to battery performance.
[0021] Optionally, the negative electrode is one or more of sodium metal, hard carbon, metal oxide negative electrode and no negative electrode current collector.
[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention aims to solve the problem that traditional inorganic fillers have little effect on the electrochemical stability window and do not have the function of modifying the electrode / electrolyte interface, and provides a nitrided nano-TiO 2 Enhanced polymer-based composite solid electrolyte, nitrided nano-TiO 2 As a functional filler, it has an interface modification effect and has the advantages of improving the mechanical properties and high conductivity of solid electrolytes.
[0023] (2) The polymer-based composite solid electrolyte of the present invention can be prepared in a simple and efficient manner, and its ionic conductivity is improved and its electrochemical stability window is widened. The ionic conductivity reaches 0.3-1.2 mS / cm, and the electrochemical stability window reaches 4.3-5.5 V. At the same time, it can promote the formation of a good SEI and improve the interface stability between the electrolyte and the electrode.
[0024] (3) In some embodiments of the present invention, a low-temperature, easy-to-operate plasma technology is used to treat TiO 2 The nitriding process can improve the particle agglomeration problem caused by high-temperature calcination. In the nitriding process, not only nitrogen can be introduced, but also the etching effect of argon gas can help to form a new type of TiO 2 Mesopores are created on the surface, thereby increasing its specific surface area (as shown in Figure 2), which helps to achieve better performance.
[0025] (4) The present invention adds nitrided nano-TiO 2 Fillers can help reduce the crystallinity of the polymer matrix and enhance the mobility of the polymer matrix chain segments, thereby improving ionic conductivity. 2 The mesoporous structure can increase the interface contact area between the filler and the polymer. The interface polarization effect between the filler with high dielectric properties and the polymer matrix can effectively reduce the activation energy and increase the number of ion migration. 2 During the cycle process, it can participate in the formation of SEI film, balance the interface electron distribution, effectively inhibit the growth of dendrites, reduce the interface resistance, and thus improve the interface stability between the electrolyte and the negative electrode.
[0026] (5) The sodium solid-state battery of the present invention can stably cycle 1200 times at room temperature at a 2C rate, with a capacity retention rate of 83.64%, and is matched with a high-load positive electrode of 12 mg cm -2It can run stably for 500 circles, and has great practical prospects and good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The nitrided TiO2 prepared in Example 1 of the present invention 2 SEM images of nanofillers.
[0028] Figure 2a The nitrided TiO2 prepared in Example 1 of the present invention 2 Surface area of nanofillers and untreated commercial nano-TiO2.
[0029] Figure 2b The nitrided TiO2 prepared in Example 1 of the present invention 2 Pore size distribution of nanofillers and untreated commercial nano-titanium dioxide, where dV / dQ represents the differential data of pore volume to pore diameter.
[0030] Figure 3 The nitrided TiO2 prepared in Example 1 of the present invention 2 Elemental analysis spectrum of nanofillers.
[0031] Figure 4 is a SEM image of the polymer-based composite solid electrolyte prepared in Example 1 of the present invention.
[0032] Figure 5 This is a SEM image of a cross section of the polymer-based composite solid electrolyte prepared in Example 1 of the present invention.
[0033] Figure 6 It is the ionic conductivity of the polymer-based composite solid electrolyte prepared in Example 1 and Comparative Examples 1 and 4 of the present invention.
[0034] Figure 7 It is the electrochemical window of the polymer-based composite solid electrolyte prepared in Examples 1, 11, 13 and Comparative Examples 2-4 of the present invention.
[0035] Figure 8 The room temperature electrochemical performance of the button cells assembled with the polymer-based composite solid electrolyte prepared in Example 1 and Comparative Example 2 of the present invention.
[0036] Fig. 9 The room temperature electrochemical performance of the polymer-based composite solid electrolyte assembled button-type battery prepared in Example 1 of the present invention at high surface capacity.
[0037] Fig.10 These are optical photographs of the polymer-based composite solid electrolyte membranes prepared in Example 1 and Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0038] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other. Unless otherwise specified, the percentages below refer to volume percentages.
[0039] Example 1 The preparation method of the polymer-based composite solid electrolyte of this embodiment comprises the following steps: (1) Place commercial nano-titanium dioxide (<200 nm) in a microwave plasma chemical vapor deposition device and adjust the N 2 and Ar pressure valve, so that N 2 The concentration of the mixed gas was 15 vol%, and the total gas flow was controlled to be 50 mL / min. The treatment temperature of the regulating device was 300 °C, the plasma treatment power was controlled to be 200 W, and the pressure was 0.2 Pa. The plasma treatment was carried out for 1 h to obtain nitrided TiO 2 Nanofillers (such as Figure 1 , 2, 3). Among them, Figure 2 uses a specific surface tester to measure the surface area of commercial nano titanium dioxide and nitride TiO 2 Nanofiller test obtained.
[0040] (2) In an atmosphere-protected environment, weigh the raw materials according to the following formula: 1 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) with a weight average molecular weight of 40W, 0.6 g of sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), 1 ml of N,N-dimethylformamide (DMF), and 3 ml of acetone (AC); then place PVDF-HFP, NaTFSI, DMF, and AC in a serum bottle and stir. Set the temperature to 60°C and the stirring speed to 800 r / min until PVDF-HFP is completely dissolved to obtain a polymer solution; (3) The nitrided TiO obtained in step (1) 2 0.12 g of nanofiller was added to the polymer solution obtained in step (2), and ultrasonic dispersion was performed with stirring. The temperature was set to 60° C., the stirring speed was 800 r / min, and the stirring time was 6 h to obtain a uniform mixed polymer solution. (4) The mixed polymer solution obtained in step (3) is cast on a glass plate, and coated with a scraper with a thickness of 1000 μm to form a film, which is then placed in a vacuum oven and the residual solvent is removed by a gradient heating method. Specifically, the film is first placed at 40° C. for 0.5 h; then heated to 50° C. and baked for 2 h; then heated to 60° C. and dried for 1 h to obtain a nitrided TiO 2 Enhanced polymer-based composite solid electrolytes (e.g. Figure 4 , 5 ).
[0041] The polymer-based composite solid electrolyte obtained in step (4) was cut into discs with a diameter of 19 mm. The room temperature ionic conductivity of the polymer-based composite solid electrolyte was tested using the Metrology Autolab (frequency 10 6 ~10 -1 ) and electrochemical window (scan rate of 1 mV / s) (e.g. Figure 6 , 7 ).
[0042] The sodium metal button-type solid-state battery of composite sodium iron phosphate (NFPP) was assembled in the stacking order of positive electrode sheet, polymer-based composite solid electrolyte and negative electrode (sodium metal sheet), and the electrochemical performance of the battery (such as Figure 8 , 9 ); Among them, the preparation method of the positive electrode sheet is as follows: the positive electrode material (NFPP), the conductive agent (SP) and the binder (PVDF, HSV900, molecular weight 90W) are stirred and mixed evenly in a mass ratio of 8:1:1, and then coated on the carbon-coated aluminum current collector with a 200μm thick scraper, placed in a vacuum oven at a temperature of 80°C and vacuum dried for 12 hours, then taken out and cut with a cutter with a diameter of 12mm to obtain the positive electrode sheet.
[0043] The test results show that the obtained polymer-based composite solid electrolyte is a dense and continuous film (see Fig.10 ), there are no obvious defects on the surface and cross section; the obtained sodium solid-state battery can stably cycle 1200 times at room temperature at 2C rate, and the capacity retention rate reaches 83.64%; matching high-load positive electrode 12mg cm -2 It can run stably for 500 cycles, and the capacity retention rate is as high as 79.64%.
[0044] Example 2 Compared with Example 1, most of the above are the same, except that N in step (1) 2 The concentration was changed to 5 vol%.
[0045] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.
[0046] Example 3 Compared with Example 1, most of the above are the same, except that N in step (1) 2 The concentration was changed to 30 vol%.
[0047] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.
[0048] Example 4 Compared with Example 1, most of the contents are the same, except that the processing temperature of the plasma chemical vapor deposition device in step (1) is changed to 200°C.
[0049] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.
[0050] Example 5 Compared with Example 1, most of the contents are the same, except that the processing temperature of the plasma chemical vapor deposition device in step (1) is changed to 250°C.
[0051] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.
[0052] Example 6 Compared with Example 1, most of the aspects are the same, except that the processing temperature of the plasma chemical vapor deposition device in step (1) is changed to 400°C.
[0053] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.
[0054] Example 7 Compared with Example 1, most of the contents are the same, except that the reaction time of the plasma chemical vapor deposition device in step (1) is changed to 0.5 h.
[0055] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.
[0056] Example 8 Compared with Example 1, most of the contents are the same, except that the reaction time of the plasma chemical vapor deposition device in step (1) is changed to 2 hours.
[0057] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.
[0058] Example 9 Compared with Example 1, most of the above are the same, except that the nitrided TiO 2 The amount of nanofiller added was changed to 0.025 g.
[0059] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.
[0060] Example 10 Compared with Example 1, most of the above are the same, except that the nitrided TiO 2 The amount of nanofiller added was changed to 0.08 g.
[0061] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.
[0062] Embodiment 11 Compared with Example 1, most of the above are the same, except that the nitrided TiO 2 The amount of nanofiller added was changed to 0.2 g.
[0063] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.
[0064] Example 12 Compared with Example 1, most of the aspects are the same, except that the gradient heating method of step (4) is changed to 30°C for 1 hour; then heated to 50°C for baking for 2 hours; then heated to 70°C for drying for 0.2 hours.
[0065] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.
[0066] Embodiment 13 Compared with Example 1, most of the aspects are the same, except that the gradient heating method of step (4) is changed to 25°C for 2 hours; then heated to 45°C for 2 hours; then heated to 60°C for 1 hour.
[0067] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this embodiment were tested. The test results are shown in Table 1.
[0068] Comparative Example 1 Compared with Example 1, most of the above are the same, except that step (1) is omitted, and the filler added in step (3) is replaced by untreated commercial nano titanium dioxide filler to obtain unnitrided TiO 2 Filler polymer based composite solid electrolyte.
[0069] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this comparative example were tested. The test results are shown in Table 1.
[0070] Comparative Example 2 Compared with Example 1, most of the above are the same, except that the processing atmosphere in step (1) is composed of argon (Ar) and nitrogen (N 2 ) mixed gas to nitrogen (N 2).
[0071] The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this comparative example were tested. The test results are shown in Table 1.
[0072] Comparative Example 3 Compared with Example 1, most of the above are the same, except that the nitrided TiO 2 The weighing amount of the nanofiller was changed to 0.25 g. The ionic conductivity, electrochemical window and button cell cycle performance of the composite solid electrolyte of this comparative example were tested. The test results are shown in Table 1.
[0073] Comparative Example 4 Compared with Example 1, most of the contents are the same, except that the gradient heating method in step (4) is changed to a conventional baking method, baking at 60° C. for 12 h.
[0074] The test results of ionic conductivity, electrochemical window and button cell cycle performance of this comparative example are shown in Table 1:
[0075] As shown in Table 1, when the composite electrolyte in Comparative Example 1 is added with unnitrided nano-TiO 2 When the filler is added, the ionic conductivity in the composite electrolyte is 0.174 mS / cm, the electrochemical window is only 4.1V, and the capacity retention rate of the solid-state sodium metal button battery with NFPP positive electrode is only 12.1% after 1000 cycles at room temperature and 2C conditions (the capacity drops at 645 cycles). 2 The nanofiller nitridation process uses pure N without Ar gas. 2 After 342 cycles, the battery capacity decays to 0, and the target of 1000 cycles cannot be achieved (e.g. Figure 8 ). Comparative Example 3 shows that the nitride TiO 2 When there are too many nanofillers, the cycle performance of the obtained sodium solid-state battery is significantly reduced, and the capacity retention rate after 1000 cycles at room temperature and 2C conditions is only 37.37%. Comparative Example 4 shows that in the process of preparing the electrolyte membrane, the conventional constant temperature baking mode is used to remove the residual solvent. The ionic conductivity and electrochemical window of the composite electrolyte membrane are significantly lower than the gradient temperature drying mode used in the embodiment. It also shows a poor cycle performance. The possible reason is that when it is baked directly under high temperature conditions, under the condition of high solvent content, the surface solvent evaporates rapidly to form a film, and the film formation uniformity is poor. Under vacuum conditions, pore fusion will occur during the internal solvent volatilization process, the filler distribution uniformity becomes poor, and bubbling, stratification and other phenomena occur (such as Fig.10), making it difficult for polymer-based solid electrolytes to exhibit good performance. Examples 1-3 show that in TiO 2 During the nitridation of nanofillers, the ratio of gas components in the plasma is quite important. As the nitrogen concentration increases, the TiO 2 The nanofiller has a higher degree of nitridation and significantly improved cycle stability. 2 When the concentration is 15%, the capacity retention rate after 1000 cycles at room temperature and 2C conditions is 91.54%, the electrochemical window is as high as 5.8V, and the ionic conductivity of the composite solid electrolyte is close to 10 -3 S / cm level, and then increase N 2 When the concentration of TiO 2 The plasma treatment temperature and treatment time during the nitridation of nanofillers also affect the TiO 2 The degree of nitridation of the nanofiller is an important factor, and its parameter setting needs to be focused on, which also affects the performance of the prepared electrolyte membrane and solid-state battery. Examples 1, 9, 10, 11, 12, and 13 show that in the process of electrolyte preparation, adding an appropriate amount of nitrided TiO 2 Nanofillers and gradient temperature increase method to remove solvent components in the membrane preparation process will obtain a composite solid electrolyte membrane with excellent ionic conductivity and electrochemical window, while also showing excellent cycling performance.
[0076] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.
Claims
1. A polymer-based composite solid electrolyte, characterized in that: The invention comprises, by weight, 8-12 parts of an olefin polymer, 4-8 parts of a sodium salt, and 0.2-2.4 parts of a filler, wherein the filler is nitrided nano-TiO2; wherein the nitrided nano-TiO2 is prepared by the following method: in a mixed gas of argon and nitrogen, plasma-treating TiO2 powder at 200-400° C. for 0.1-2 hours to obtain nitrided nano-TiO2; The concentration of nitrogen in the mixed gas is 5-30 vol%, the flow rate of the mixed gas is 40-60 ml / min, the pressure is 0.18-0.45 Pa, and the power of the plasma treatment is 200-450 W.
2. The polymer-based composite solid electrolyte according to claim 1, characterized in that The vinyl polymer is one or more of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene) copolymer, poly(vinylidene fluoride-trifluoroethylene) copolymer, poly(vinylidene fluoride-tetrafluoroethylene) copolymer and poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) copolymer.
3. The polymer-based composite solid electrolyte according to claim 1, characterized in that The sodium salt is one or more of sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, sodium hexafluorophosphate, sodium difluorophosphate, sodium tetrafluoroborate, sodium difluorooxalatoborate, sodium bisoxalatoborate and sodium perchlorate.
4. The polymer-based composite solid electrolyte according to claim 1, characterized in that The thickness of the polymer-based composite solid electrolyte is 20-200 μm.
5. The method for preparing a polymer-based composite solid electrolyte according to any one of claims 1 to 4, characterized in that: The steps include: S1. Mix the vinyl polymer, sodium salt, filler, and polar solvent in a ratio of 8-12 g: 4-8 g: 0.2-2.4 g: 20-60 ml to obtain a polymer solution; S2. Casting the polymer solution on a mold, removing the solvent, and obtaining a polymer-based composite solid electrolyte.
6. The preparation method according to claim 5, wherein in S1, the polar solvent is one or more of tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, acetone, and 2,2,2-trifluoro-N,N-dimethylacetamide; or, in S1, the olefinic polymer, sodium salt, filler, and polar solvent are mixed and stirred at 45-80° C. for 6-14 hours.
7. The preparation method according to claim 5, wherein in S2, when removing the solvent, the mixture is first dried at 25-45°C for 0.2-2 hours, then dried at 40-60°C for 0.5-3 hours, and then dried at 55-80°C for 1-5 hours.
8. A sodium solid-state battery, characterized in that: The invention comprises a positive electrode sheet stacked in sequence, a polymer-based composite solid electrolyte according to any one of claims 1 to 4 or a polymer-based composite solid electrolyte prepared by the preparation method according to any one of claims 5 to 7, and a negative electrode.
Citation Information
Patent Citations
Surface-lithiated metal oxide nanoparticles for li battery electrolytes
CA2560837A1
Polymer sodium ion solid electrolyte as well as preparation method and application thereof
CN116315074A
Enhanced modified coating for lithium battery diaphragm, preparation method thereof and lithium battery diaphragm
CN116435712A
Deposition of tio2 thin film using discharge plasma
JP2000313962A
Porous thin-film electrode constituted of titania particle and its reforming method
JP2006310134A
Cited By
Polymer-based composite solid electrolyte, preparation method and lithium solid-state battery
CN120709472A
Polymer-based composite solid electrolyte, preparation method and lithium solid-state battery
CN120709472B
Solid polymer electrolyte membrane and preparation method and application thereof
CN121282336A
A roll-mill-sand-mill combined preparation method of sub-micron sulfide solid electrolyte
CN122638598A